2019
DOI: 10.1088/1741-4326/ab313f
|View full text |Cite
|
Sign up to set email alerts
|

The local nature of the plasma response to cold pulses with electron and ion heating at ASDEX Upgrade

Abstract: In low density Ohmic heated tokamak plasmas a fast increase of the

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 39 publications
1
35
0
Order By: Relevance
“…Remarkable agreement with experimental transport phenomena has been found in many cases (e.g. Angioni et al 2019;Rodriguez-Fernandez et al 2019;Luda et al 2020), and database studies have suggested that physics-based models of heating and transport perform equally as well as, if not better than, empirical scalings in predicting performance in present devices. Integrated simulations are now routinely used to inform and optimize the design of SPARC.…”
Section: Integrated Modelling Of Sparc Plasmassupporting
confidence: 58%
See 2 more Smart Citations
“…Remarkable agreement with experimental transport phenomena has been found in many cases (e.g. Angioni et al 2019;Rodriguez-Fernandez et al 2019;Luda et al 2020), and database studies have suggested that physics-based models of heating and transport perform equally as well as, if not better than, empirical scalings in predicting performance in present devices. Integrated simulations are now routinely used to inform and optimize the design of SPARC.…”
Section: Integrated Modelling Of Sparc Plasmassupporting
confidence: 58%
“…The development and validation of theory-based reduced models and integrated modelling frameworks in recent years (Kinsey et al 2011;Citrin et al 2017;Kim et al 2017;Meneghini et al 2017;Linder et al 2018;Rodriguez-Fernandez et al 2018;Angioni et al 2019;White 2019) have allowed physic-based simulations to also inform the design of SPARC during the early stages of its development. This paper presents results from both empirical scalings and integrated modelling simulations of SPARC plasmas, with a focus on evaluating fusion gain with theory-based models and assessing the sensitivity to plasma physics assumptions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model could also explain the disappearance of the temperature inversion effect at high density [33 and references therein], the trend with plasma current [35], the spatial correlation between temperature flex point and rational surfaces [36,9], and the connection to thermal coupling between ions and electrons [12]. Recent work at ASDEX Upgrade [37] shows that the effect of auxiliary heating on cold-pulse behavior [5,38,39,40,6] can also be explained by local models like TGLF, as well as the fast reduction of normalized core density gradient following the cold-pulse injection.…”
Section: Cold-pulse Phenomenology and Open Questionsmentioning
confidence: 99%
“…It is believed that the heat flux in magnetically confined high temperature plasmas cannot be expressed by the simplest "Fick's law", where the heat flux is modeled to be proportional to the local temperature gradient [1]. Instead, a wide variety of models, including the diffusion-convection model [2][3][4][5], the critical gradient model [6,7], nonlocal models [8][9][10][11][12][13][14], models including off-diagonal contribution [15][16][17], and others were developed for comprehensively describing the complicated transport phenomena.…”
Section: Introductionmentioning
confidence: 99%